If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(x + -4) + x(3 + -2x) = 0 Reorder the terms: 2x(-4 + x) + x(3 + -2x) = 0 (-4 * 2x + x * 2x) + x(3 + -2x) = 0 (-8x + 2x2) + x(3 + -2x) = 0 -8x + 2x2 + (3 * x + -2x * x) = 0 -8x + 2x2 + (3x + -2x2) = 0 Reorder the terms: -8x + 3x + 2x2 + -2x2 = 0 Combine like terms: -8x + 3x = -5x -5x + 2x2 + -2x2 = 0 Combine like terms: 2x2 + -2x2 = 0 -5x + 0 = 0 -5x = 0 Solving -5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-5'. x = 0 Simplifying x = 0
| 13r+4-7r= | | -2+ln(x-4)=4 | | 5x+10x+5=25 | | 5x+10x+5=25 | | 5x+10x+5=25 | | 2B-6=4B | | 3-(3x-8)=4y-5 | | (4c-6c+5)(4c-2c-1)= | | lnx-2lnx=3 | | 6x-4=20x+3 | | 6x-23+x+54=180 | | 4x+2x(x+4)= | | -4x-6(-2+4)=64 | | 2x+y-z=7z | | -4x-6(-2+4)=64 | | 3x-1=-3x+3 | | 3x-1=-3x+3 | | -5x+-2=-2X+4 | | -6x-5(-3x-3)=60 | | 114=2x+3x | | 5x+7y=3890 | | 8x+7y-5-5x+6y-3= | | -2x-2(-5x-4)=-80 | | 15+4y-1=15y-13-2y | | y+(y-2)2=2 | | 3x-n=7+n | | 25-13=3(x-1) | | -13.9=b+17.1 | | r+7= | | 15-44=3(x-4)-5 | | 3x+(x-5)=15+4 | | -16+13=m-2 |